2009
DOI: 10.4049/jimmunol.0900908
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Dendritic Cell-Induced Immune Responses Mediated by the Novel C-Type Lectin Receptor mDCAR1

Abstract: The dendritic cell (DC) immunoreceptors (DCIR) and DC-immunoactivating receptors (DCAR) represent a subfamily of cell surface C-type lectin receptors (CLR), whose multifunctional capacities range from classical Ag uptake and immunoregulatory mechanisms to the involvement in DC ontogeny. On the basis of the generation of specific mAbs, we functionally characterized mouse DCAR1 (mDCAR1) as a member of the DCIR/DCAR family. Expression of mDCAR1 was strongly tissue dependent. mDCAR1 expression on DCs was restricte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 47 publications
2
34
0
Order By: Relevance
“…Recently, it has been shown that MDL-1 binds dengue virus and induces production of TNF-a in macrophages but whether this occurs by signaling through Syk has yet to be formally demonstrated (Chen et al, 2008). Finally, mDCAR and mDCAR-1 in mouse may constitute additional Syk-coupled myeloid activatory CLRs that associate with FcRg although their ligands and function at present remains unknown (Kaden et al, 2009;Kanazawa et al, 2003). There is no direct ortholog of mDCAR or mDCAR-1 in human but they are closely related to human BDCA-2 (blood dendritic cell antigen 2), which is expressed in plasmacytoid DCs (Dzionek et al, 2000(Dzionek et al, , 2001.…”
Section: Itam Signalingmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, it has been shown that MDL-1 binds dengue virus and induces production of TNF-a in macrophages but whether this occurs by signaling through Syk has yet to be formally demonstrated (Chen et al, 2008). Finally, mDCAR and mDCAR-1 in mouse may constitute additional Syk-coupled myeloid activatory CLRs that associate with FcRg although their ligands and function at present remains unknown (Kaden et al, 2009;Kanazawa et al, 2003). There is no direct ortholog of mDCAR or mDCAR-1 in human but they are closely related to human BDCA-2 (blood dendritic cell antigen 2), which is expressed in plasmacytoid DCs (Dzionek et al, 2000(Dzionek et al, , 2001.…”
Section: Itam Signalingmentioning
confidence: 94%
“…When crosslinked by monoclonal antibodies, DCIR inhibits TLR8-mediated induction of IL-12 and TNF-a by myeloid DCs and TLR9-induced IFN-a production by plasmacytoid DCs ). In mouse, there are four DCIR homologs (mDCIR and mDCIR2-4) but only mDCIR and mDCIR2 (also known as 33D1) possess an ITIM (Kaden et al, 2009). Their function is not known but mDCIR-deficient mice develop autoimmunity and marked expansion of the DC compartment (Fujikado et al, 2008).…”
Section: Itim Signalingmentioning
confidence: 98%
“…When antigen is targeted to DCAR1, another C-type lectin expressed on CD8 + DCs, the antigen is internalised, presented on both MHC class I and II, and strong antibody responses are induced even in the absence of adjuvants [37]. This is not a general feature of C-type lectins because Clec12A, another C-type lectin-like molecule on CD8 + DCs, is much less efficient at inducing CD4 T cell proliferation and antibody production [23,38].…”
Section: Which DC Subset Should Be Targeted?mentioning
confidence: 98%
“…In many studies, targeting antigens to a range of DC surface molecules does not appear to require DC activation stimuli to induce strong antibody responses. These molecules include MHC class I [44] and II [20], FcgRII [44], CD45 [45], CD45RA [45], CD4 [45], CIRE [35], FIRE [35], mannose receptor [11], DCAR1 [37] and Clec9A [23,36]. In addition, low level antibody responses are often obtained even on targeting molecules such as DEC-205 that depend on adjuvants for a full response [23].…”
Section: Reviewmentioning
confidence: 99%
“…The DCIR on monocyte-derived DCs is internalized efficiently after trigger-ing with a DCIR-specific monoclonal antibody (8). Four homologs of human DCIR are present in the mouse genome (DCIR1-4), but only DCIR1 and DCIR2 possess the immunoreceptor tyrosine-based inhibitory motif sequence (9). Mouse DCIR1 is expressed in B cells, monocytes, macrophages, and DCs (6).…”
mentioning
confidence: 99%